Mini-Mental State Examination in Brazil: An Item Response Theory Analysis - Melo, Denise Mendonça de; Barbosa, Altemir José Gonçalves; Castro, Nelimar Ribeiro de; Neri, Anita Liberalesso (Paidéia (Ribeirão Preto), 2020)
The Mini-Mental State Examination (MMSE) is currently used to the track cognitive status of older adults in Brazil. Studies on its psychometric properties are lacking, especially ones that use Item Response Theory. The objective was to assess the difficulty of the items in a Brazilian version of MMSE using the Rasch model and to identify possible differential item functioning (DIF), considering schooling, age and sex of the sample of Brazilian older adults. This study used the answers of 2.734 older adults to the 30 items of MMSE. It was found that four items in the seven series were the most difficult, and items nine, 13, 22 and 23 were the easiest. The skill of respondents was higher than the items’ difficulty level. DIF was observed for schooling, sex and age in, respectively, 27, 18 and 16 items. It is concluded that the use of MMSE in Brazilian older adults should be cautious due to the large number of biased items, mainly due to schooling.